Application of electrician skill course based on EPIP - Kedong Lyu (Jurnal Taman Vokasi, 2018)
EPIP is a new engineering education mode, and it is different from the traditional engineering education modes, which is based on vocational education engineering practice. EPIP stands for engineering, practice, innovation, and project. EPIP method proved effective in vocational education engineering practice. After analyzing the steps of EPIP, an application example of EPIP is presented to show what is EPIP, how it works, how to solve the problem of the traditional engineering education and how to transform a traditional electrician skill course to EPIP electrician skill course. EPIP electrician skill course has been tested in the experimental class. The experiment shows that EPIP has improved the innovation capability of students in the electrician skill. EPIP has a certain application value in vocational education. Finally, the paper discusses how to promote EPIP and to improve vocational education.